The Questioning Rewriting of Biblical Myths in a Selection of Stories from Memorias de la luna oscura (2021), by Ana Lucía Fonseca - Rojas González , José Pablo (2024)
The purpose of this article is to present an analysis of the rewriting work that Costa Rican author Ana Lucía Fonseca does of some exemplary biblical narratives, to give voice to figures that, from her perspective, represent dissidence, heresy, exile, rebellion, and persecution. We focus on the stories “La amante de Eva” and “Caín y las semillas”. For the analysis, we follow the contributions of Herrero Cecilia (2006), who understands the myth —within a rewriting work— as a “reference intertext”, which is interpreted and reformulated by a writer in a new text. Consequently, we consider, in relation to the new texts, the transformations —by inclusion or exclusion— that are introduced in their narrative schemes (always in relation to the “intertexts of reference”), as well as the ideological line that underlies in the specific message, in each of them.